Core-shell structured Co3O4@PPy composite for electrochemical determination of terbutylhydroquinone. Issue 46 (18th October 2022) - Zhang, Yuxi; Wang, Cunli; Zhao, Yalin; Yu, Zhe; Yang, Fengchun; Zhang, Xin
Abstract : TBHQ is a significant synthetic antioxidant, but excessive use of TBHQ is harmful to human health. Abstract : TBHQ is a significant synthetic antioxidant, but excessive use of TBHQ is harmful to human health. Therefore, the preparation of a high-efficiency TBHQ electrochemical sensor is of great significance. In this work, a core–shell structured Co3 O4 @PPy composite is synthesized for TBHQ determination and exhibits remarkable electrochemical properties. The core–shell structure of Co3 O4 @PPy composite shows the synergistic effects of fast charge transfer, rich active surface area and more active sites. Under optimal conditions, the linear range of the developed sensor is 0.2–600 μM, and the detection limit is 0.05 μM (S/N = 3). In addition, it also has good stability and reproducibility due to the stable protective role of the PPy shell. The proposed sensor can also be applied to practical sample detection.